Tarifas de importaç\~ao e evas\~ao fiscal no Brasil - Honorio Kume; Guida Piani; Pedro Miranda (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– Tax evasion in Brazilian imports has been an issue of concern for the customs authorities. This problem is addressed here using the theoretical approach of defining evasion as the difference between the value of exports of other countries to Brazil and value of imports reported by Brazil. This makes it possible to quantify the effects of high import tariff rates on tax evasion due mainly to underreporting of value. The main empirical result of the paper is that a one-percentage-point increase in the tariff rate implies a 3.1% increase in evasion. Furthermore, we identify an also robust elasticity of evasion of 3.2% for differentiated products in contrast with a lower value of 2.2% for homogeneous products.
Keywords: H26; 330; Import; Steuerstrafrecht; Brasilien